RENDERING ARCHAISMS AND HISTORISMS IN FRENCH-UZBEK TRANSLATIONS (BASED ON THE TRANSLATIONS BY B. ERMATOV) - Sadriddinova Dildora Mamadjanovna (International Journal of Literature and Language Studies, 2026)
This article examines the peculiarities of translating archaisms and historisms from French into Uzbek, based on the translation practice of B. Ermatov. The study aims to identify the main translation strategies employed when working with obsolete vocabulary, and to evaluate the degree to which stylistic and historico-cultural information is preserved in the translated texts. The methodological framework of the study is grounded in comparative-contrastive and contextual analysis. The findings demonstrate that the translator employs both native Uzbek archaic equivalents and transliteration with descriptive commentary, thereby achieving a balance between authenticity and accessibility for the reader